Rethinking the Role of Clinical Practice Guidelines in Pharmacy Education - Brown, Daniel L. (Am J Pharm Educ, 2015)
Clinical practice guidelines (CPGs) play a major role in pharmacy education. Students learn to locate, retrieve, and apply CPGs in didactic coursework and practice experiences. However, they often memorize and quote recommendations without critical analysis, which tends to undermine their clinical growth. Students should become genuine drug experts, based on strong critical-thinking skills and the ability to assimilate extensive clinical and scientific knowledge. Clinical practice guidelines improve health care, and students should be familiar with them, but there are legitimate criticisms of CPGs, stemming largely from potential conflicts of interest and limitations in the quality and scope of available evidence. Despite such flaws, CPGs can be used to facilitate the clinical growth of students if the emphasis is placed on critically analyzing and evaluating CPG recommendations, as opposed to blindly accepting them. From that perspective, the role that CPGs have come to play in education may need to be reconsidered.